Proton MR Spectroscopy in Children with Bipolar Affective Disorder: Preliminary Observations - Castillo, Mauricio; Kwock, Lester; Courvoisie, Helen; Hooper, Stephen R. (American Journal of Neuroradiology, 2000)
BACKGROUND AND PURPOSE: Bipolar affective disorder (BPAD) can have its onset during childhood, but the diagnosis may be difficult to establish on the basis of clinical findings alone. Our purpose was to determine whether proton MR spectroscopy can be used to identify abnormalities in the brain of children with BPAD.METHODS: Ten children, ages 6 to 12 years, underwent clinical testing to establish the diagnosis of BPAD. After a drug washout period, all patients underwent MR spectroscopy in which a TE of 135 was used along with a single-voxel placement in both frontal and temporal lobes during a single session. Peaks from N-acetylaspartate (NAA), choline (Cho), glutamate/glutamine (Glu/Gln), and lipids were normalized with respect to the creatine (Cr) peak to obtain ratios of values of peak areas. These data were compared with those obtained in 10 non–age-matched control subjects. To corroborate our data, five children with BPAD also underwent 2D MR spectroscopic studies of the frontal lobes with parameters similar to those used in the single-volume studies.RESULTS: All children with BPAD had elevated levels of Glu/Gln in both frontal lobes and basal ganglia relative to the control group. Children with BPAD had elevated lipid levels in the frontal lobes but not in the temporal lobes. Levels of NAA and Cho were similar for all locations in both groups. Two-dimensional MR spectroscopic studies in five children with BPAD confirmed the presence of elevated lipids in the frontal lobes.CONCLUSION: Our preliminary observations suggest that MR spectroscopy may show abnormalities in children with BPAD not found in unaffected control subjects. It remains to be established whether these abnormalities are a signature of the disease and can be used as a screening test.